The effects of zinc supplementation on the TNF-α profile and diarrhea in severely malnourished children of low income family (Medical Journal of Indonesia, 2003)
Zinc deficiency has a great impact on growth and development, especially in malnourished children. Zinc is important in both local and systemic immunity. The aim of this study was to assess the impact of zinc supplementation on the cytokine, tumor necrosis factor α (TNF-α), and diarrhea in severely undernourished under-five children of low-income families. A randomized double blind pre-test post-test controlled design was selected. A group of 12-59 month-old children were given local food, and treated as control group (n=60), and another group (n=60) were given local food with 15 mg/5 ml zinc as intervention group. Zinc concentration was measured by atomic absorption spectrophotometer (AAS), and TNF-α concentration was determined by ELISA. Data on nutrient intakes were collected using 24-hour food recall method. The result of the study showed that after zinc intervention, zinc serum increased significantly, and TNF-α concentration decreased along with reduction of the duration and frequency of diarrhea. Zinc concentration increased 87.0% in the intervention group, while in the control group the increase was only 19.6%. There was a significant reduction of both serum and fecal TNF-α concentration after intervention (p<0.05). Severity and duration of diarrhea were reduced significantly in the intervention group compared to the control group (p<0.001). It was concluded that zinc intervention reduced the duration and severity of diarrhea through improvement of immunity, especially local immunity with TNF-α as biomarker. (Med J Indones 2003; 12: 247-51)